Resolving the Polynymy of Place: or, how to create a gazetteer of colonized landscapes ... - FAULL, KATHERINE; Jakacki, Diane (unknown, 2018)
This paper will explore the problem of creating a gazetteer of colonized landscapes, specifically those of the mid-Atlantic in the 18th century, in which the name of a place (toponym) changes depending on the person or political entity who is describing that place. In colonized landscapes, there can be multiple names for one place. Maps of this period are veritable palimpsests of conquests and defeats; and travel diaries, mission records and letters contain accounts of human experience of places that are multiply identified. The task is made more complicated still when one factors time into the equation: when competing spatial identities persist across generations. The paper proposes a two-phased approach to developing the Moravian Lives gazetteer, which will expand geographically to places beyond North America and will need to resolve polynymic complexities in Central Europe, the Arctic areas of Greenland and Newfoundland, the Caribbean, South Africa and Australia. ...